Outcomes of non-surgical treatment of chronic anal fissure: A comparative study - Muhammed Dewana, Azhy; Saeed Ahmed, Baderkhan; Abdulkadir Baban, Ahmed; Haweizy, Rawand Musheer (Zanco Journal of Medical Sciences (ZJMS), 2023)
Background and objective: Chronic anal fissure is a common health problem related to high morbidity. The chemical option for treating chronic anal fissures is highly preferred. Methods: A clinical prospective comparative study was carried out in the General Surgery Outpatient Department in Rizgary Teaching Hospital, Erbil, KRG, during the period from January 2019 to December 2021,on a sample of 100 patients randomly recruited patients with chronic anal fissures divided into two groups with 50 participants each: the DTZ group, who received 2% diltiazem ointment, and the GTN group, who used 0.2% glyceryl trinitrate ointment twice daily for 6 consecutive weeks. The aim of the study is to compare the efficacy and effects of topical Diltiazem (DTZ) and topical glyceryl trinitrate (GTN) in the management of chronic anal fissures. Results: There was a highly significant association between fissure healing at the 4th week and patients treated with DTZ (P <0.001). A highly significant association was observed at the 6th week between fissure healing and DTZ treatment (P <0.001), while there was later a highly significant association between fissure healing at the 8th week and patients treated with GTN (P <0.001). A significant association was observed between treatment adverse effects and patients treated with GTN (P = 0.05). DTZ was found to be more effective for symptomatic relief than GTN. Conclusion: Both DTZ and GTN are effective in the treatment of chronic anal fissures, but treatment with DTZ is accompanied by faster healing and lower side effects.